Intellectus agens triplex distinguitur: Early Franciscans and Avicenna in Petrus Hispanus' Theory of the Agent Intellect in the Scientia libri de anima - Meirinhos, José (2021)
The understanding of the nature and functions of the intellect became one of the main problems of the 13th-century Latin reception of Aristotle's De anima, which highlighted similar difficulties to those already felt by the Greek and Arab commentators in their struggle with those brief, laconic, cryptic pages where that faculty of the soul is discussed. Those early difficulties were increased by the reception of this theory in the already doctrinally-saturated vocabulary of the Augustinian tradition, where the demands of Christian theology and anthropology dominated the understanding of the soul-body relationship, perception, and the explanation of the activity of the rational soul as illumination. Petrus Hispanus' Scientia libri de anima addresses those difficulties with a long-winded theory of the faculties of the soul, which silently appropriates Avicenna's Liber de anima and other sources so as to explain human life, sensation, and knowledge. Here we discuss the explanation of the agent intellect, which allows us to observe how John of La Rochelle and Franciscan philosophy more generally inspired Petrus Hispanus' position.